Effectiveness of Health Promotion Media (Posters) on Reducing Blood Sugar Levels in Diabetes Mellitus Patients - Rotua Sumihar Sitorus; Megawati Sinambela; Reni Aprinawaty Sirait; Herlina Herlina (Jurnal Keperawatan Priority, 2026)
Diabetes Mellitus is a chronic metabolic disorder characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Health promotion plays a pivotal role in enhancing patient knowledge and self-management behaviors. Among various educational tools, posters are considered effective media due to their ability to convey complex health messages visually and concisely. This study aimed to evaluate the effectiveness of poster-based health promotion interventions in reducing blood glucose levels among patients with Diabetes Mellitus at the Bandar Khalifah Public Health Center. This research employed a quantitative method utilizing a quasi-experimental design with a one-group pretest-posttest approach. A sample of 52 respondents was selected using a random sampling technique. Data were analyzed using the Paired Sample t-test to determine the statistical significance of the intervention. The statistical analysis revealed a significant difference in blood glucose levels before and after the intervention, with a p-value of 0.006 (p < 0.05). These findings indicate that the implementation of visual health education significantly contributed to the reduction of blood glucose levels among the respondents. It is concluded that poster-based media is an effective tool for supporting glycemic control in patients with Diabetes Mellitus. Therefore, it is recommended that healthcare providers utilize and develop diverse visual health promotion media regularly to sustain public awareness and foster long-term healthy behaviors.